Good Sunday!

This blog will show how to transform polar equations, in the form of r(θ) to a pair of parametric equations, x(t) and y(t).

Tools We Need

x = r * cos θ

y = r * sin θ

Let θ = t.

For each example, we will change each polar equation and display a graph for each form. The polar form, colored blue, is on top; the parametric form, in red, is on the bottom. (A TI nSpire-CX is used for the pictures)

Example (I):

r = 2*θ

Then θ = r/2 and let θ = t.

x = r * cos t

x = 2 * t * cos(r/2)

x = 2 * t * cos((2*t)/2)

x = 2 * t * cos t

Similarly,

y = r * sin t

y = 2 * t * sin(r/2)

y = 2 * t * sin t

To summarize:

r = 2*θ

is equivalent to

x = 2 * t * cos t

y = 2 * t * sin t

Example (II):

r = e^(2 * θ)

Then θ = 1/2 * ln r and let θ = t.

And...

x = r * cos t

x = e^(2*t) * cos(1/2 * ln r)

x = e^(2*t) * cos(1/2 * ln(e^(2*t)))

x = e^(2*t) * cos(1/2 * 2 * t)

x = e^(2*t) * cos t

y = r * sin t

y = e^(2*t) * sin(1/2 * ln r)

y = e^(2*t) * sin(1/2 * ln(e^(2*t)))

y = e^(2*t) * sin t

To summarize:

r = e^(2*θ)

is equivalent to:

x = e^(2*t) * cos t

y = e^(2*t) * sin t

Example (III):

r = 2 cos θ

Then:

θ = arccos(r/2) = cos⁻¹(r/2)

Then, with θ=t...

x = r * cos t

x = 2 * cos t * cos(cos⁻¹(r/2))

x = 2 * cos t * cos(cos⁻¹(2*cos(t)/2))

x = 2 * cos t * cos t

x = 2 * cos² t

And... (some trigonometric identities are required)

y = r * sin t

y = 2 * cos t * sin(cos⁻¹(r/2))

Note: sin(cos⁻¹ x) = √(1 - x²)

y = 2 * cos t * √((1 - (r/2)²)

y = 2 * cos t * √(1 - r²/4)

y = 2 * cos t * √(1 - (4 cos² t)/4)

y = 2 * cos t * √(1 - cos² t)

Note: sin² x + cos² x = 1

y = 2 * cos t * sin t

Note: sin(2*x) = 2 * cos x * sin x

y = sin (2*t)

To Summarize:

r = 2 cos θ

is equivalent to:

x = 2 * cos² t

y = sin (2*t)

Until next time, take care!

Eddie

This blog is property of Edward Shore. 2013